MEDIA PEMBELAJARAN KLASIFIKASI HEWAN BERDASARKAN JENIS MAKANAN BERBASIS AUGMENTED REALITY - Amanda Ayu Puspitasari; Dwi Ratnawati (Jurnal Pendidikan Teknologi Informasi (JUKANTI), 2025)
This research develops Augmented Reality-based learning media for classifying animals based on food type for junior high school students. This research aims to answer the challenges of science learning which is often less interesting and interactive. Augmented Reality technology was chosen to visualize animals in 3D, strengthen conceptual understanding, and increase student engagement. Augmented Reality technology allows students to view 3D animal visualizations interactively, providing a more interesting and enjoyable learning experience. This research methodology uses the Research and Development (R&D) model with the ADDIE approach (Analysis, Design, Development, Implementation, Evaluation). learning materials. Learning media is tested for suitability through validation from material experts, media experts, and student responses. The validation results show that the material aspect received a score of 85% and the media aspect received a score of 83%, both categorized as "Very Eligible". Student testing resulted in an 89% satisfaction rate, also in the “Very Worth It” category. In conclusion, this Augmented Reality-based learning media is effective and practical in increasing students' understanding of animal classification. This application also makes learning easier, which can be done anytime and anywhere via a smartphone device.